Cervico-vaginal secretion cytokine profile: A non-invasive approach to study the endometrial receptivity in IVF cycles. - Zanotta, Nunzia; Monasta, Lorenzo; Skerk, Kristina; Luppi, Stefania; Martinelli, Monica; Ricci, Giuseppe; Comar, Manola (Am J Reprod Immunol, 2019)
PROBLEM: Cytokines have a significant role in the process of embryo implantation, trophoblast growth, and differentiation by modulating the immune and endocrine system. The aim of this study was to investigate the profile of a large set of cytokines in the cervico-vaginal washing of women undergoing IVF, to explore the association of these proteins with a good receptive endometrium. METHOD OF STUDY: A cohort of 155 women scheduled for IVF cycle was recruited. All patients were asymptomatic for genitourinary infections and had been screened for chlamydia, mycoplasma, and other bacterial infections. All IVF subjects were treated according to standard clinical and laboratory protocols. A panel of 48 immune factors was analyzed on cervico-vaginal washing, using magnetic bead-based multiplex immunoassays (Bio-Plex, BIO-RAD Laboratories, Milano, Italy). RESULTS: A total of 99 patients reached embryo transfer, of which 31 had a clinical pregnancy. A pattern of four pro-inflammatory immune molecules, IL-12p40, IFN-a, MIF, and MCP3 (P < 0.001), was found significantly up-regulated in the cervico-vaginal fluid of women with clinical pregnancy. A significantly increased expression of IL-9, Gro , and SDF-1 (P < 0.05) was observed in the presence of endometriosis, while high levels of IL-13 and L-15 were associated with ovulatory infertility factor (P < 0.05). CONCLUSION: In this pilot study, we demonstrated that the expression of specific cytokines in the cervico-vaginal washing on the day of oocyte retrieval might have a positive correlation with the potential clinical pregnancy. Therefore, cervico-vaginal secretion cytokine profiling might be a new, non-invasive approach to study the endometrial receptivity in IVF management.